Kent Monkman : entre ré/appropriation et « Painting Back ». - Pancaldi, Valentina (Artelogie. Recherche sur les arts, le patrimoine et la littérature de l'Amérique latine, 2018)
À la suite d’une série d’évènements historiques de grande relevance sociopolitique, les années 1990 ont connu une montée d'initiatives menées par les artistes autochtones nord-américains visant à une récupération et une divulgation de leur l’héritage culturel, et, de ce fait, à une revendication de leur visibilité dans le panorama international. De cette résurgence, l’artiste multimédial autochtone canadien, Kent Monkman, constitue l’une des voix plus actives et plus emblématiques. En créant un dialogue épistémologique entre les études postcoloniales et l’art autochtone, cet article interrogera l’œuvre de Kent Monkman au prisme d’une notion dont sera proposée une définition, à savoir le « Painting Back ».
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; _Nettoyé

Control mapping: Peter Pitseolak and Zacharias Kunuk on reclaiming Inuit photographic images and imaging - Winfield, Norman David (Decolonization: Indigeneity, Education & Society, 2014)
Inuit have been participating in the development of photo-reproductive media since at least the 19th century, and indeed much earlier if we continue on Michelle Raheja’s suggestion that there is much more behind Nanook’s smile than Robert Flaherty would have us believe. This paper examines how photographer Peter Pitseolak (1902-1973) and filmmaker Zacharias Kunuk have employed photography and film in relation to Raheja’s notion of “visual sovereignty” as a process of infiltrating media of representational control, altering their principles to visualize Indigenous ownership of their images. For camera-based media, this pertains as much to conceptions of time, continuity and “presence,” as to the broader dynamics of creative retellings. This paper will attempt to address such media-ontological shifts – in Pitseolak’s altered position as photographer and the effect this had on his images and the “presence” of his subjects, and in Kunuk’s staging of oral histories and, through the nature of film as an experience of “cinematic time,” composing time in a way that speaks to Inuit worldviews and life patterns – as radical renegotiations of the mediating properties of photography and film. In that they displace the Western camera’s hegemonic framing and time-based structures, repositioning Inuit “presence” and relations to land within the fundamental conditions of photo-reproduction, this paper will address these works from a position of decolonial media aesthetics, considering the effects of their works as opening up not only for more holistic, community-grounded representation models, but for expanding these relations to land and time directly into the expanded sensory field of media technologies.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé